Manipulation of the Innate Immune Response by Varicella Zoster Virus - Gerada, Chelsea; Campbell, Tessa M.; Kennedy, Jarrod J.; McSharry, Brian P.; Steain, Megan; Slobedman, Barry; Abendroth, Allison (Frontiers in Immunology, 2020)
Varicella zoster virus (VZV) is the causative agent of chickenpox (varicella) and shingles (herpes zoster). VZV and other members of the herpesvirus family are distinguished by their ability to establish a latent infection, with the potential to reactivate and spread virus to other susceptible individuals. This lifelong relationship continually subjects VZV to the host immune system and as such VZV has evolved a plethora of strategies to evade and manipulate the immune response. This review will focus on our current understanding of the innate anti-viral control mechanisms faced by VZV. We will also discuss the diverse array of strategies employed by VZV to regulate these innate immune responses and highlight new knowledge on the interactions between VZV and human innate immune cells.